The Holocene and Upper Pleistocene pollen sequence of Carihuela Cave, southern Spain - Fernández, Santiago; Fuentes, Noemí; Carrión, José S.; González-Sampériz, Penélope; Montoya, Encarna; Gil, Graciela; Vega-Toscano, Gerardo; Riquelme, José a. (Geobios, 2007)
A new pollen sequence (ca. 15,700–1250 yr BP) is presented for three stratigraphical sections of Carihuela Cave (Granada, southeastern Spain), thus completing a record that covers from the last Interglacial to late Holocene. The Late Glacial is characterized by open landscapes with junipers and early colonisation of Quercus, while the Holocene is depicted by mixed oak forests, with a diversity of broad-leaf trees and scrub, which decrease after ca. 5470 yr BP synchronously with the expansion of xerophytes and occurrence of indicators of anthropogenic disturbance. The whole pollen record of Carihuela ﬁts into the general trends described for reference pollen sites of southern Europe, including Padul in the province of Granada, and other sequences from Mediterranean Spain, through which the heterogeneity of environmental change increases from mid to late Holocene. We conclude that, in contrast with other regions of Spain, deciduous Quercus-dominated forests are very old in eastern Andalusia, thus conﬂicting with ﬂoristic phytosociological models of vegetation change that imply that monospeciﬁc Q. ilex/ rotundifolia woodlands are the potential mature forest in the region. Dating results suggest that the last Neanderthals of Carihuela lived between ca. 28,440 and 21,430 yr BP, which agrees with the postulation that southern Spain was the latest refugium for this human species in Europe
Keywords: historical biogeography; Holocene; palaeoecology; Spain; Upper Pleistocene; vegetation history